2021
DOI: 10.1186/s13046-021-02042-1
|View full text |Cite|
|
Sign up to set email alerts
|

Complement inhibitor CSMD1 modulates epidermal growth factor receptor oncogenic signaling and sensitizes breast cancer cells to chemotherapy

Abstract: Background Human CUB and Sushi multiple domains 1 (CSMD1) is a large membrane-bound tumor suppressor in breast cancer. The current study aimed to elucidate the molecular mechanism underlying the effect of CSMD1 in highly invasive triple negative breast cancer (TNBC). Methods We examined the antitumor action of CSMD1 in three TNBC cell lines overexpressing CSMD1, MDA-MB-231, BT-20 and MDA-MB-486, in vitro using scanning electron microscopy, proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Using Bonferroni’s multiple testing correction (adjusted p -value = 0.05/(508 × 7856) = 1.25 × 10 −8 ), there were 3790 significant TSG-GOBP pairs in the result of DCG analysis ( Table 2 and Supplementary Table S5 ). The most significantly enriched term in the obtained results was “mRNA processing” (GO:0006397), and the input genes were obtained from DCGs with CSMD1, which has a tumor-suppressive function [ 39 ]. The RNA processing related to GO terms, such as mRNA metabolic process (GO:0016071), RNA splicing (GO:0008380), and regulation of RNA splicing (GO:0043484), were found to be enriched significantly in several TSGs (see Supplementary Table S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Using Bonferroni’s multiple testing correction (adjusted p -value = 0.05/(508 × 7856) = 1.25 × 10 −8 ), there were 3790 significant TSG-GOBP pairs in the result of DCG analysis ( Table 2 and Supplementary Table S5 ). The most significantly enriched term in the obtained results was “mRNA processing” (GO:0006397), and the input genes were obtained from DCGs with CSMD1, which has a tumor-suppressive function [ 39 ]. The RNA processing related to GO terms, such as mRNA metabolic process (GO:0016071), RNA splicing (GO:0008380), and regulation of RNA splicing (GO:0043484), were found to be enriched significantly in several TSGs (see Supplementary Table S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, patients with mutated TP53 had worse OS and relapse-free survival times ( 45 ). CSMD1 is considered to be a tumor suppressor gene in many types of cancer, such as breast cancer ( 46 ), colorectal cancer ( 47 ), gastric cancer ( 48 ) and HCC ( 49 ); thus, the mutation of the CSMD1 may cause the proliferation of the cancer. One published article revealed that the mutation of CSMD1 may promote the progression of esophageal cancer ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…The low expression of CSMD1 was also associated with reduced survival in the breast cancer METABRIC study [ 68 ]. Gialeli et al suggested that CSMD1 provides tumour suppression by interacting with the EGFR pathway and can be used as a biomarker for predicting chemotherapy response in highly invasive breast cancer [ 69 ]. Additionally, Tang et al discovered that the decreased expression of CSMD1 in melanoma cells has a lower influence on melanoma cell migration and proliferation, and that CSMD1 can serve as a tumour suppressor gene in melanoma cells [ 13 ].…”
Section: Csmd1 Functionmentioning
confidence: 99%